Pelatihan Ecoprint Seabagai Pemberdayaan Ibu-Ibu PKK RT 05 RW 09 Kelurahan Karangpoh Kota Surabaya - Azhar, Whenny Ismiati; Septiawati, Rizka; Hutabarat, Ruth Eviana; Nilasari, Aprillia (Abimanyu : Jornal of Community Engagement, 2022)
Ecoprint technique is an alternative home industry in the form of environmentally friendly textile products, ecoprint itself is a batik technique using stems, leaves, flowers that can produce color pigments. PKK RT 05 women, who do not yet have skills in producing an item will be able to use their free time to increase their income through community service activities in the form of training on making ecoprints. The purpose of this service is to increase knowledge, skills, and hone skills for partners in the process of making ecoprints. 1) socialization to mothers regarding the meaning of ecoprint and the materials and tools needed, 2) training to mothers with the practice of making ecoprints, 3) digital marketing socialization for marketing and developing ecoprint finished products so that they can help increase income. At the socialization stage This is done by socializing ecoprint as an environmentally friendly product and introducing what materials and tools are used in the process of making ecoprints. The ecoprint-making process training went through several stages: washing the cloth with soap until it was clean, arranging the desired stem, leaf, flower motifs, pounding it with tools, re-washing the cloth after it was pounded using alum solution, drying the cloth to dry, and producing ecoprints into a product. product.